Timing of return to work and women's breastfeeding practices in urban Malaysia: A qualitative study. (30th May 2017) - Sulaiman, Zaharah; Liamputtong, Pranee; Amir, Lisa H.
Abstract: Nearly half of the working population in Malaysia are women, and with only a short period of maternity leave, they may struggle to achieve the recommended 6 months of exclusive breastfeeding. The aim of this paper was to explore the relationship between the timing of return to work and beliefs and breastfeeding practices among women in urban Malaysia. A qualitative inquiry based on a phenomenological framework and multiple methods was used: face‐to‐face interview, participant diary and researcher field notes. Data collection took place in Penang and the Klang Valley, Malaysia, from March to September 2011. Eligible participants were purposely identified at randomly selected recruitment sites. A thematic analysis method was used to develop the typologies and categories of the findings. A total of 40 working women with a mean age of 32 years (SD 3.4) were interviewed and 15 participated in the diary writing. Most women (75%) returned to work between 2 and 3 months. Only 10% returned to work 4 months or later postpartum, and 15% had an early return to work (defined here as less than 2 months). The women fell into three groups: Passionate women with a strong determination to breastfeed, who exclusively breastfed for 6 months; Ambivalent women, who commenced breastfeeding but were unable to sustain this after returning to work; and Equivalent women, who perceived formula feeding as equally nutritious as breast milk. Although longer maternity leave was very important for Ambivalent women to maintain breastfeeding, it was not as important for the Equivalent or Passionate women. In conclusion, returning earlier was not an absolute barrier to continuing breastfeeding. Instead, a woman's beliefs and perceptions of breastfeeding were more important than the timing of her return to work in determining her ability to maintain breastfeeding or breast milk feeding.